FOOD AID TO CONFLICT AFFECTED POPULATIONS WFP EMERGENCY OPERATION - THE CASE OF EASTERN UKRAINE - Tamburelli, Gianfranco (Proceedings of National Aviation University, 2016)
The increase in the number of areas where humanitarian emergencies are brought about by armed conflicts, and the enduring nature of these situations, call for research aimed at clarifying the international legal framework for food-aid operations, taking into account the developments and practices in the fields of human rights, humanitarian law, environmental law, and cooperation for sustainable development. In this article, therefore, the Author analyses the general problems of food aid in conflict areas, with a focus on a concrete situation, namely the crisis in Eastern Ukraine. The dramatic situation faced by some Ukrainian regions - where, since the spring of 2014, the World Food Programme (WFP), various other international organizations, the EU and some National Development Cooperations have been operating - underlines, in fact, the importance of reaching a clear understanding of all the different regulatory levels in the field of food aid security and safety.